2011
DOI: 10.1074/jbc.m110.192534
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor-1 Receptor Transactivation Modulates the Inflammatory and Proliferative Responses of Neurotensin in Human Colonic Epithelial Cells

Abstract: sion. This is the first report to indicate that NT transactivates IGF-1R and that this response is linked to Akt phosphorylation and NF-B activation, contributing to both pro-inflammatory and tissue repair signaling pathways in response to NT in colonic epithelial cells. We propose that IGF-1R activation represents a previously unrecognized key pathway involved in the mechanisms by which NT and NTR1 modulate colonic inflammation and inflammatory bowel disease. Neurotensin (NT)4 is a 13-amino acid neuropeptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 61 publications
(88 reference statements)
3
37
1
Order By: Relevance
“…At the molecular level, this MCH requirement for costimulators could perhaps be explained by the fact that G protein-coupled receptors, like MCHR1, lack intrinsic kinase activity, and thus they need to transactivate growth factor receptors to convey mitogenic and growth signals (12). For instance, it has been previously shown that neurotensin promotes the growth of colonic epithelial cells via IGF-1R transactivation (49) and substance P promotes the proliferation of U-373MG astroglioma cells via EGFR transactivation (7).…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, this MCH requirement for costimulators could perhaps be explained by the fact that G protein-coupled receptors, like MCHR1, lack intrinsic kinase activity, and thus they need to transactivate growth factor receptors to convey mitogenic and growth signals (12). For instance, it has been previously shown that neurotensin promotes the growth of colonic epithelial cells via IGF-1R transactivation (49) and substance P promotes the proliferation of U-373MG astroglioma cells via EGFR transactivation (7).…”
Section: Discussionmentioning
confidence: 99%
“…35,36 IGF-IR is a key regulator of tumor development which plays vital roles in regulating cell proliferation, differentiation and survival. 37,38 We and others' labs have demonstrated that IGF-IR promotes angiogenesis and tumor growth through the PI3K/ AKT downstream pathway. [39][40][41] Moreover, we found that IGF-IR also functioned in the process of chemoresistance to oxaliplatin, a first-line regimen for CRC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1R has been identified as a key regulator of tumor development by regulating cell proliferation, differentiation and survival (31,32). Upregulated expression of IGF-1R has been observed in numerous human malignancies (12).…”
Section: Discussionmentioning
confidence: 99%